2014
DOI: 10.1007/s00276-013-1252-8
|View full text |Cite
|
Sign up to set email alerts
|

Internal supravesical hernia accompanied with anomalous fold formations: a cadaveric case report

Abstract: During the abdominal dissection of a 67-year-old male cadaver, an unusual peritoneal fold was encountered on the inner surface of the anterior abdominal wall. The peritoneal fold had two parts: the anterior part was located at the midsagittal plane including dispersed urachus remnants, the other part was located at the coronal plane with a triangular shape at the posterior edge of the sagittal part. Remnants of the umbilical arteries were ascending in the lateral margins of the coronal part. Accordingly, two p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Another theory is that supravesical hernia is caused by an extraordinarily large medial umbilical fold congenitally that creates a pocket above the bladder [17] . Ozturk et al indicated that there was a developmental anomaly of the urinary system in their cadaveric case [18] . However, the pathogenesis has not yet been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Another theory is that supravesical hernia is caused by an extraordinarily large medial umbilical fold congenitally that creates a pocket above the bladder [17] . Ozturk et al indicated that there was a developmental anomaly of the urinary system in their cadaveric case [18] . However, the pathogenesis has not yet been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Another theory is that Supravesical hernia is caused by an extraordinarily large medial umbilical fold congenitally that creates a pocket above the bladder [11]. Ozturk et al indicted that there was a developmental anomaly of the urinary system in their cadaveric case [12]. However the pathogenesis has not yet been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…[12] Other factors associated with this type of hernia are increased expression of umbilical folds that lead to the formation of a deeper peritoneal depression of the paravesical space into which the surrounding abdominal structures can protrude. [10,13] Inadequate collagen synthesis (congenital or acquired) leads to weakness and multiple damage to the fascial and aponeurotic structures of the anterior abdominal wall. [10,14] The intravesical type of internal supravesical hernia occurs when the apex of the bladder is weakened by defective closure of the urachus which results in formation of diverticulum that can herniate directly into the bladder.…”
Section: Discussionmentioning
confidence: 99%